Nuansa Paralelisme dalam Teks Pariwisata Mahasiswa Universitas Negeri Makassar - Azis Azis; Juanda Juanda (Seminar Nasional LP2M UNM, 2022)
Abstract. Parallelism in the form of words, phrases, and sequences in sentences is one of the very basic parts to explore the meaning of the contents of the text. The advantage of this research is that it emphasizes parallelism in the form of words, phrases, and series of sentences. The research data is in the form of tourism texts for Indonesian Language and Literature Education students, Faculty of Language and Literature, Universitas Negeri Makassar. The research was carried out for 7 months in 2022. The focus is on the nuances of parallelism with the design of the text study. Data collection technique is documentation. The data obtained in the field are described and analyzed based on content analysis which includes nuances of tourism text parallelism from the aspect of word parallelism, phrase parallelism, sentence series parallelism. The results of the study show the nuances of parallelism at the word level, there are 15 parallelisms, at the phrase level there are 8 parallelisms, and at the sentence series only 5 parallelism levels. The lack of use of parallelism in student tourism texts is evidence that students do not yet have adequate knowledge in writing tourism texts that contain parallelism. Parallelism of tourism texts in the form of the word alteration’pergantian’, even though’meski’, maintained ‘terawat’, travel ‘perjalanan’; phrases high cliff ‘tebing-tebing tinggi’, hot water’air panan’; series in the sentence Galung waterfall ‘air terjun Galung’.   Keywords: Nuance, Parallelism, Words, Phrases, And Sentences